Nouvelles identifications concernant trois enluminures du livre d’Heures de Claude d’Urfé (Rome, 1549, Huntington Library, San Marino, HM 1102) - Manuel Lalanne (Les Cahiers de l'École du Louvre)
Claude d’Urfé was above all known for his Château de La Bâtie d’Urfé whose Italianism is often highlighted. It is not, however, the only one of his commissions with an Italian influence. A book of hours in the collections of the Huntington Library of San Marino, California, produced for him in 1549, when he was the ambassador of Henri II to Rome, constitutes important evidence for the understanding of the diplomat’s tastes. In this manuscript, copies of compositions with sources in Roman churches can be identified; these illuminations thus bear the trace of what the ambassador saw and appreciated during his Roman sojourn. Following Isabelle Balsamo’s work of identification, we propose three new sources and further consider the attribution of the book of hours.